Решите уравнение:
(3x-4)(4x+1) - (6x+1)(2x-3) = 8

galina060876 galina060876    2   22.01.2022 04:23    0

Ответы
mathewkichunov mathewkichunov  22.01.2022 06:00

x=4

Пошаговое объяснение:

(3x-4)(4x+1) - (6x+1)(2x-3) = 8

12x²+3x-16x-4-12x²+18x-2x+3=8

3х-16х+18х-2х=8+4-3

3х=9

x=3

ПОКАЗАТЬ ОТВЕТЫ

x = 3

Пошаговое объяснение:

(3x-4)(4x+1) - (6x+1)(2x-3) = 8

12x²+ 3x - 16x - 4 - 12x² + 18x - 2x + 3=8

3x - 1 = 8

3x = 8+1

3x = 9

x = 9:3

x = 3

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика